Analysis of Gen Z's Level of Understanding in Using Social Media Wisely and Safely - Evika; Asiah; Erwita Ika Violina (CV. Eracita Grup, 2025)
This study aims to describe the level of understanding among Generation Z in using social media wisely and safely, particularly in relation to digital ethics, account security, information verification skills, and positive social media engagement. The research employed a descriptive quantitative method using a Likert-scale questionnaire consisting of 20 statements distributed online to 51 respondents. The data were analyzed using frequency percentages to identify response tendencies for each indicator. The findings show that respondents demonstrate a high level of understanding, especially in polite communication, careful information sharing, awareness of digital risks, and the ability to maintain privacy and account security. However, several aspects remain weak, including limiting social media usage time and the habit of reporting negative content. These results indicate that Generation Z possesses good digital literacy, yet the application of healthy digital behavior is not fully optimal. Therefore, more practical and continuous digital literacy education is needed to ensure that the understanding gained can be consistently applied in daily digital activities.